Violence in Hasmonean Judea: Skeletal evidence of a massacre from 2nd–1st century BCE Jerusalem. (18th January 2022) - Dittmar, Jenna M.; Nagar, Yossi; Arbiv, Kfir; Lieberman, Tehillah; Mitchell, Piers D.
Abstract: During a salvage excavation conducted by the Israel Antiquities Authority, a mass grave containing the skeletal remains from 124 individuals, many with evidence of weapon injuries, was discovered in a water cistern outside the Old City of Jerusalem. Radiocarbon dates derived from human bone and the date of the material finds suggest the skeletal remains date to the end of the 2nd century or the beginning of the 1st century BCE. The aim of this research is to analyze the weapon injuries in order to reconstruct the nature and context of this violence. The human skeletal remains from 23 individuals recovered from the cistern were selectively retained and examined macroscopically in a laboratory setting. Silicone casts of selected weapon injuries ( n  = 5) were analyzed using scanning electron microscopy. Numerous examples of peri‐mortem blunt‐ and sharp‐force trauma were observed including evidence that at least 16 individuals were decapitated. The extent and nature of the observed injuries as well as the evidence of their haphazard deposition into the cistern suggest that these individuals were the victims of a massacre. As a highly visible act of violence, massacres are often used as a mechanism for social control. When contextualized, this skeletal assemblage is most likely evidence of a massacre that occurred during the reign of the Hasmonean king Alexander Jannaeus. This is the first archeological evidence for the use of socially sanctioned violence to legitimize the Hasmonean state and to maintain social control at the end of the 2nd century–early 1st century BCE.